Suspected Ticagrelor-Induced Bullous Fixed Drug Eruption - Kawall, Tiffany (Cureus, 2021)
We describe a case of a suspected cutaneous hypersensitivity reaction to ticagrelor. The patient displayed a localized bullous fixed drug eruption after being loaded with ticagrelor, which resolved with oral antihistamines and topical steroids after one week. Clopidogrel and rivaroxaban were successfully administered as alternative antithrombotic therapy without any apparent further hypersensitivity skin reaction.